Transparency Of Village Government In Preparing Village Revenue And Expenditure Budget In Sampali Village, Deli Serdang Regency: Transparansi Pemerintah Desa Dalam Penyusunan Anggaran Pendapatan Dan Belanja Desa Di Desa Sampali, Kabupaten Deli Serdang - Rejeki Karina Banurea; Theresia Mardiyana Tamba; Miming Kartika Olivia Silitonga; Julia Ivanna (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Transparency is a crucial aspect of governance, requiring the government to provide information regarding the use of state assets to the public. This study aims to examine the transparency of the village government in preparing the village revenue and expenditure budget (APBDes) with specific objectives in Sampali Village, Deli Serdang Regency. This study employed a qualitative descriptive method to describe and understand the phenomenon studied in depth within its context. The results indicate that the Village Budget (APBDes) preparation process in Sampali Village was carried out procedurally in accordance with applicable regulations. This process began with an open and inclusive village meeting (Musrenbang) involving the village head, hamlet head, PKK (Family Welfare Movement) administrators, Posyandu (Integrated Service Post) cadres, the Village Consultative Body (BPD), and the Community Empowerment Institute (LPM) as representatives of various elements of the village government and the community. All budget utilization plans were discussed and agreed upon in this forum, and the results were recorded in minutes as the legal basis for the official preparation of the APBDes.